1999
DOI: 10.1007/bf02236356
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic plane of separation between external anal sphincter and puborectalis muscle

Abstract: An anatomic plane of separation is present between the puborectalis muscle and the external sphincter. The presence of this plane is important to help understand the diffusion of some suppurative anal lesions and to plan advanced sphincter-sparing procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 17 publications
1
19
0
Order By: Relevance
“…Within the U‐shaped levator hiatus formed by the puborectalis, lie the urethra, the vagina in females and the anal canal. Defects in any one, two or all three components of the anal sphincter complex may cause fecal incontinence secondary to anal sphincter dysfunction32, 33. The sonographic approach used in this paper can assist in diagnosing tears in all three components.…”
Section: Discussionmentioning
confidence: 99%
“…Within the U‐shaped levator hiatus formed by the puborectalis, lie the urethra, the vagina in females and the anal canal. Defects in any one, two or all three components of the anal sphincter complex may cause fecal incontinence secondary to anal sphincter dysfunction32, 33. The sonographic approach used in this paper can assist in diagnosing tears in all three components.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] This separation is marked by a cleft in adult anatomic specimens 1 and by a depression palpable at mid anal canal in the living subjects. 5 A plane of separation can be identified and developed, endoanally, at this level.…”
mentioning
confidence: 99%
“…5 A plane of separation can be identified and developed, endoanally, at this level. 4 These muscles also have distinct, as well as quite separate, innervations. Direct branches of sacral roots running in their inner surface supply the levator muscles, whereas the pudendal nerve, which runs laterally and externally to them, innervates the external sphincter 3,6 The possible existence of a functional as well as anatomic separation between the two muscles suggested that one try to remove the rectum (along anatomic boundaries using a combined abdominoendoanal approach) together with a large portion of the levator muscles while preserving the lower anal canal and the external sphincter with its innervation (a major functional structure in the voluntary continence mechanism).…”
mentioning
confidence: 99%
“…In addition to a layer of muscles with mainly sphincteric functions, a second layer has developed into a well-marked diaphragm, which constitutes a muscular and tendinous sheet attached to the inner circumference of the pelvis [Fritsch 1995, Occelli 2001, Pit 2003]. In this pel- [Marani et al 1993, Fucini, 1999, Marani 2002.…”
Section: Review Of the Literaturementioning
confidence: 99%